Cold meat [videorecording (DVD)] - Drouin, Sébastien; Desmond, Andrew; Kermack, James; Barton-Steel, James; Leech, Allen; Bergman, Nina; Tual, Yan; Banzer, Riley (Level 33 Entertainment, 2024)
While passing through the Colorado Rockies, David stops for a meal at a diner and ends up heroically saving a young waitress from her violent ex-husband. David hits the road again amid a dangerous blizzard, and one false move sends him into a ravine in the eye of the storm. Slowly running out of resources, it's hard to tell what will get him first: the cold or the beast prowling outside.